Heat transfer optimization in hybrid nanofluid flow over a convectively heated stretching/shrinking sheet considering different nanoparticle shapes - Yahaya, Rusya Iryanti; Mustafa, Mohd Shafie; Md Arifin, Norihan (2025)
A sophisticated statistical tool called the response surface methodology (RSM) can be utilized to find the optimal settings for efficient heat performance of hybrid nanofluids with various flow conditions. The present study examines the steady flow of Ag-MgO/H2O hybrid nanofluid over a permeable stretching/shrinking sheet. The effects of chemical reaction, activation energy, magnetic field, various nanoparticle shapes, zero mass flux, velocity slip, and convective boundary condition are incorporated into the flow problem. Similarity variables are then used to transform the governing partial differential equations and boundary conditions into non-linear ordinary differential equations. These equations are solved numerically using the bvp4c solver in MATLAB, and optimization is conducted using the RSM in Minitab. Hybrid nanofluid with platelet- and spherical-shaped nanoparticles is found to have the lowest local skin friction coefficient in the stretching and shrinking cases, respectively. Meanwhile, the augmentation of the suction parameter () and Biot number () improves the local Nusselt number. Through the RSM, the local Nusselt number is estimated to be optimized at and . With the desirability of 100%, the local Nusselt numbers for the stretching and shrinking cases are approximated to be maximized at 0.68501 and 0.68493, respectively.